The Extracts of Morinda officinalis and Its Hairy Roots Attenuate Dextran Sodium Sulfate-Induced Chronic Ulcerative Colitis in Mice by Regulating Inflammation and Lymphocyte Apoptosis - Liang, Jian; Liang, Jiwang; Hao, Hairong; Lin, Huan; Wang, Peng; Wu, Yanfang; Jiang, Xiaoli; Fu, Chaodi; Li, Qian; Ding, Ping; Liu, Huazhen; Xiong, Qingping; et al. (Frontiers in Immunology, 2017)
Morinda officinalis is beneficial for the treatment of inflammatory bowel disease (IBD). The hairy-root with higher genetic and biochemical stability cultured from Morinda officinalis might have similar effects to treat IBD. In this study, the main chemical composition of the root extracts of Morinda officinalis (MORE) native plant and the hairy root extract of Morinda. officinalis (MOHRE) was compared by quantitative HPLC. And difference of their therapeutic effects and potential mechanism were evaluated using 3% dextran sodium sulfate (DSS)-induced chronic colitis in mice and T lymphocytes in vitro. The results found MOHRE possesses many specific peaks unobserved in the chromatogram of native plant. The content of iridoids in the MORE (3.10%) and MOHRE (3.01%) are somewhat similar but quite different for their anthraquinones’s content (0.14% and 0.66%, respectively). Despite all this, treatment with both MORE and MOHRE significantly attenuated the symptoms of colitis, including diarrhea, body weight, colon shortening, histological damage and decreased inflammatory cytokine levels. In addition, they dose-dependently increased the apoptosis of T lymphocyte in vivo and in vitro. And, the differences for treatment effects on ulcerative colitis (UC) between them both in this study were mostly insignificant. The results demonstrated that the effects of MORE and MOHRE for treatment of UC are similar, although there are a few difference on their chemical composition, indicating the hairy-root cultured from Morinda officinalis might be able to replace its native plant on treatment of UC. The successful derivation of a sustainable hairy root culture provides a model system to study the synthetic pathways for bioactive metabolites, which will make the use of bioreactors to largely produce traditional medicine become reality.